Investigation of Effect of Extensively Used Polymers on Thermoreversible Properties of Pluronic ® Tri-Block Polymer - Rarokar, Nilesh Ramesh; Saoji1, Suprit D; Khedekar, Pramod (Fakultas Farmasi, Universitas Gadjah Mada, 2017)
This investigation presents a study on the effect of various polymers on gelling properties of tri-block (Pluronic®) copolymers and increasing the stability parameter of in situ gelling system by altering their composition. The tri-block copolymers finds their importance in fabrication of in situ gelling system for the delivery of various kinds of drugs, which can be administered by topical, ophthalmic or parenteral routes. Pluronic®, is a category of non-toxic, water soluble, biodegradable poly (ethylene oxide)/poly (propylene oxide)/poly ethylene oxide), tri-block copolymers which have application in formulation of various in situ gelling systems. This formulation undergo thermo-reversible gelation, where it exists as a free flowing liquid at low temperature and gels in the range of body temperature to form stable depot in aqueous environment. Gelling system was prepared according to the 'Cold Method' using different concentration of polymers (15% to 20% w/v) and subjected to the determination of gelation temperature (GT), viscosity study and effect of various polymers on the strength of gelation. Overall study on the gelation of system at particular temperature is the important parameter for formulation of in situ drug delivery system. It was established that addition of 0.5% w/v of HPMC K4M into gelling system make it stable for forming gel in the range of body temperature whereas methyl cellulose, carbopol 934P, and HPMC E-5 restrict the gel formation. Key words: Tri-Block Copolymer; Gelation Temperature; Gelling System; Depot.